2015
DOI: 10.1523/jneurosci.0390-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

A Bidirectional Link between Brain Oscillations and Geometric Patterns

Abstract: Like hallucinogenic drugs, full-field flickering visual stimulation produces regular, geometric hallucinations such as radial or spiral patterns. Computational and theoretical models have revealed that the geometry of these hallucinations can be related to functional neuro-anatomy. However, while experimental evidence links both visual flicker and hallucinogenic drugs to upward and downward modulations of brain oscillatory activity, the exact relation between brain oscillations and geometric hallucinations rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Previous work has shown that the content of simple, but not complex, visual hallucinations (i.e. radial, grid or spiral patterns), can be modulated by the specific stroboscopic stimulation frequency 18,24 . As previously mentioned, stroboscopic stimulation at 3 Hz caused entrainment of this frequency, SSVEP, along with its harmonics, leading to a significant increase in theta power for 3 Hz relative to the other conditions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work has shown that the content of simple, but not complex, visual hallucinations (i.e. radial, grid or spiral patterns), can be modulated by the specific stroboscopic stimulation frequency 18,24 . As previously mentioned, stroboscopic stimulation at 3 Hz caused entrainment of this frequency, SSVEP, along with its harmonics, leading to a significant increase in theta power for 3 Hz relative to the other conditions ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further exploratory analyses were carried out to compare signal diversity measures with more standard electrophysiological measures. We computed the average spectral power profile for delta (1-4 Hz), theta (4-8 Hz), alpha (8-13 Hz) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) frequency bands, for each condition and participant. As for LZs, for each participant and condition the 10 min recording was divided into non-overlapping 10 s segments.…”
Section: Normalized Spectral Powermentioning
confidence: 99%
See 3 more Smart Citations